2016
DOI: 10.1177/0031512516631054
|View full text |Cite
|
Sign up to set email alerts
|

Development of Subcortical Pitch Representation in Three-Month-Old Chinese Infants

Abstract: This study investigated the development of subcortical pitch processing, as reflected by the scalp-recorded frequency-following response, during early infancy. Thirteen Chinese infants who were born and raised in Mandarin-speaking households were recruited to partake in this study. Through a prospective-longitudinal study design, infants were tested twice: at 1-3 days after birth and at three months of age. A set of four contrastive Mandarin pitch contours were used to elicit frequency-following responses. Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
(27 reference statements)
0
30
0
Order By: Relevance
“…Extending the knowledge of the cortically recorded AEP components, the frequency following response (FFR) component indicates that essential subcortical structures utilized for tracking pitch are functional from birth (Jeng et al, 2016a,b). Tracking the development of the FFR across time, Jeng et al (2016b) reported improved subcortical tracking accuracy and pitch strength at 3 months, supporting the hypothesis that neural circuitry involved in processing musical stimuli is refined through development and passive exposure (Jeng et al, 2016b).…”
Section: Infants Aged 0-24 Monthsmentioning
confidence: 67%
“…Extending the knowledge of the cortically recorded AEP components, the frequency following response (FFR) component indicates that essential subcortical structures utilized for tracking pitch are functional from birth (Jeng et al, 2016a,b). Tracking the development of the FFR across time, Jeng et al (2016b) reported improved subcortical tracking accuracy and pitch strength at 3 months, supporting the hypothesis that neural circuitry involved in processing musical stimuli is refined through development and passive exposure (Jeng et al, 2016b).…”
Section: Infants Aged 0-24 Monthsmentioning
confidence: 67%
“…This factor undermined the power of the conclusions and prevented the possibility of performing statistical analyses for each Mandarin tone used. Despite the limitations of the study, the findings fill a gap in understanding the developmental trajectory of subcortical processing during the first 3 months of life [25].…”
Section: Frequency Following Response: Evaluation In Infantsmentioning
confidence: 85%
“…Even at birth, children are able to detect subtle differences in verbal sounds. Newborns can effectively differentiate all the features of human speech and most infants who participated in an FFR follow-up showed improvement in pitch tracking and response amplitudes at 3 months of age [25]. Such neural refinements observed by FFR are often highlighted in the literature for both infants [22,24] and young infants [15,23].…”
Section: Frequency Following Response: Evaluation In Infantsmentioning
confidence: 88%
See 1 more Smart Citation
“…They also prefer their native tongue over unfamiliar languages (Mehler et al, 1988;Moon, Cooper, & Fifer, 1993), and discriminate between the synthesised intonation contours of unknown languages (Ramus, 2002). Well-developed subcortical pitch processing has been demonstrated in newborns aged 1 to 3 days using Mandarin tones (Jeng et al, 2016). Pitch-intervals, meanwhile, have been found to be represented in the auditory system just as in adults.…”
mentioning
confidence: 97%